Cidade em disputa : lutas de moradores e urbanismo autoritário em Belo Horizonte (Brasil) e Porto (Portugal) - 1960-1980 - Philippe Urvoy (2020)
This thesis analyses, from a comparative perspective, social conflicts around the right to housing in the popular neighborhoods of Belo Horizonte, in Brazil, and Porto, in Portugal, in the 1960s and 1970s. Such conflicts include both the emergence of grassroots neighborhood movements organized around the right to housing, including through the occupation of buildings or vacant lands, as well as state strategies of repression and social control developed in these territories. The thesis draws on a variety of sources, from mainstream and alternative press, police inquiries, documents produced by the municipal administration, and also oral sources through interviews carried out with the residents of these neighborhoods. In regards to Belo Horizonte, the research focuses on the first movement of urban land occupations launched in the early 1960s and the repression that affects these occupations - and all the favelas in the city - after the 1964 military coup. In the case of Porto, the thesis analyses the authoritarian project for the peripheral neighborhoods of the city between the end of the 1950s, under the Salazar dictatorship, and the emergence of a deep social movement initiated by the residents of these same neighborhoods after the April Revolution of 1974. In the comparison between these two cities, the urban periphery appears as a space produced in a conflictual way, a contested urban space, locus of fixation, control and repression of the poorest inhabitants of the city by the state. It is also a place where numerous struggles, revolts and social mobilizations emerges. A space of insurgencies, re-imagined by the collective experiences of its residents and reconfigured by the intervention of State power as a territory of exception, a privileged target for its repression and surveillance. The 1960s and 1970s, the period in focus at this work, reveal themselves as a crucial historical moment of this invention and production of the contemporary urban periphery within a city in dispute, between struggles of residents and authoritarian urban planning and management projects experienced by the State.